Single-cell RNA sequencing of bone marrow reveals the immune response mechanisms of lymphocytes under avian leukosis virus subgroup J infection - Cheng Liu; Yu Zhang; Ruyu Liao; Lecheng Wang; Xinyi Zhou; Min Tan; Keyun Xu; Haiwei Wang; Qigui Wang; Yongju Zhao; Zhifu Cui; Xi Lan (Poultry Science)
Avian Leukosis Virus (ALV) can induce tumorigenesis and immune suppression by acting on lymphocytes in the bone marrow. In this study, single-cell RNA sequencing (scRNA-seq) was used to analyze chicken bone marrow lymphocytes under Avian Leukosis Virus subtype J (ALV-J) infection. Using subgroup-specific marker genes and cell state analysis, we identified 18 distinct cell clusters, including 8 T cell clusters, 2 B cell clusters, 5 tumor-like cell clusters, and 3 unidentified clusters. Gene expression analysis revealed that in the 10 T/B lymphocyte clusters, the differentially expressed genes in double-positive T cells, B1-like B cells, and cytotoxic T cells were highly enriched in pathways related to viral infection and immune response. These three cell populations exhibited high proportions and significant changes after infection, suggesting a strong immune response to ALV-J infection. Additionally, during ALV-J infection, the proportion of regulatory T cells and CTLA4 T cells increased, while immune suppressive factors TGFB1 and IL16 were highly expressed across the cell populations, indicating an immune-suppressive state in bone marrow lymphocytes. Moreover, ALV-J infected all cell populations; however, within the same cluster, only a fraction of the cells expressed ALV-J viral genes. Notably, in all cells expressing ALV-J viral genes, the ''Rho family GTPase signaling pathway'' associated with antiviral responses was activated. The Rho family, which is a key regulator of cytoskeletal reorganization and cell polarity, also plays a critical role in tumor cell proliferation and metastasis. Further analysis using Ingenuity Pathway Analysis (IPA) software predicted key upstream regulators of immune response, such as MYC and MCYN. In conclusion, this study identifies key genes and signaling pathways involved in immune responses of different lymphocyte subpopulations triggered by ALV-J infection in bone marrow. These findings contribute to a better understanding of the immune mechanisms in ALV-J-infected bone marrow lymphocytes and provide insights for discovering breeding loci for ALV-J resistance.